2022
DOI: 10.5694/mja2.51455
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing HIV pre‐exposure prophylaxis for Medicare‐ineligible people in Melbourne, Australia: analysis of patients attending the PrEPMe Clinic

Abstract: To the Editor: People without Medicare coverage cannot access Pharmaceutical Benefits Scheme (PBS)-subsidised human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) or associated clinical care. Rates of HIV infection diagnosis are disproportionately higher among overseas-born gay and bisexual men compared with Australian-born gay and bisexual men. 1 In response, in June 2020, the Alfred Hospital and the Victorian Infectious Diseases Reference Laboratory established the free PrEPMe Clinic for Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, our sample was largely GBM of higher socio-economic status (evidenced through a combination of their education and employment status, though notably we did not collect income information). Recent research has found that PrEP in Australia may be too costly for those who do not have access to Medicare, so there certainly may be some GBM who may find PrEP in Australia too expensive [ 44 ]. Nonetheless, no participants in our study reported that they discontinued PrEP because they were no longer able to access it.…”
Section: Discussionmentioning
confidence: 99%
“…However, our sample was largely GBM of higher socio-economic status (evidenced through a combination of their education and employment status, though notably we did not collect income information). Recent research has found that PrEP in Australia may be too costly for those who do not have access to Medicare, so there certainly may be some GBM who may find PrEP in Australia too expensive [ 44 ]. Nonetheless, no participants in our study reported that they discontinued PrEP because they were no longer able to access it.…”
Section: Discussionmentioning
confidence: 99%
“…However, for this population, the cost of unsubsidized PrEP and limited information about PrEP relevant to their cultures and lived experiences remain an issue that needs to be addressed before new PrEP modalities become available in Australia. This indicates the need for ongoing advocacy to make PrEP free for all people irrespective of their Medicare eligibility so Australia can reach its target of virtual elimination of HIV by 2025 (19,50,51). This is to coincide with the development of culturally specific resources to be disseminated in multiple settings including universities, accommodation services, community organizations, and health services (52) to maximize coverage and impact.…”
Section: Discussionmentioning
confidence: 99%
“…Among ethnic and migrant GBMSM, including international students, studies have found that GBMSM participants were willing but did not use PrEP, in part because of the high cost of unsubsidized PrEP (1,13,18,19). For international students specifically, limited hours permitted for paid employment up to 40 h per fortnight (20), and with the Australian minimum wage of around AU$20 per hour (or US$15 per hour) before tax (21), the hesitancy to take PrEP could intersect with income level and work restrictions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation